JWST: Deuterated PAHs, PAH Nitriles, and PAH Overtone and Combination Bands. I. Program Description and First Look - C. Boersma; L. J. Allamandola; V. J. Esposito; A. Maragkoudakis; J. D. Bregman; P. Temi; T. J. Lee; R. C. Fortenberry; E. Peeters (The Astrophysical Journal, 2023)
A first look is taken at the NIRSpec 1–5 μ m observations from James Webb Space Telescope program 1591 that targets seven objects along the low-mass stellar life cycle with polycyclic aromatic hydrocarbon (PAH) emission. Spectra extracted from a 1.″5 radius circular aperture are explored, showing a wealth of features, including the 3 μ m PAH complex, the PAH continuum, and atomic and molecular emission lines from H i , He, H _2 , and other species. CO _2 - and H _2 O-ice absorption and CO emission is also seen. Focusing on the bright-PDR position in M17, the PAH CH stretch falls at 3.29 μ m (FWHM = 0.04 μ m). Signs of its 1.68 μ m overtone are confused by line emission in all targets. Multicomponent decomposition reveals a possible aliphatic deuterated PAH feature centered at 4.65 μ m (FWHM = 0.02 μ m), giving [D/H] _alip. = 31% ± 12.7%. However, there is little sign of its aromatic counterpart between 4.36 and 4.43 μ m. There is also little sign of PAH nitrile emission between 4.34 and 4.39 μ m. A PAH continuum rises from ∼1 to 3.2 μ m, after which it jumps by about a factor of 2.5 at 3.6 μ m, with bumps at 3.8, 4.04, and 4.34 μ m adding structure. The CO _2 absorption band in M17 is matched with 10:1 H _2 O:CO _2 ice at 10 K. The v = 0 pure rotational molecular hydrogen population diagram reveals >2200 K UV-pumped gas. The hydrogen Pfund series runs from levels 10 to >30. Considering Br α /Br β = 0.381 ± 0.01966 and Case B recombination results in A _V ≃ 8. CO emission in IRAS 21282+5050 originates from 258 K gas. In-depth spectral–spatial analysis of all features and targets is planned for a series of forthcoming papers.